ETIKA BISNIS ISLAM (TELAAH SURAT AL-ISRA’ AYAT 35, HUD : 84, DAN SURAT AL-‘ARAF AYAT : 34 TENTANG MEMENUHI TAKARAN DALAM TIMBANGAN) - M Arif Al Kausari (el-'Umdah, 2021)
Abstract : Fulfilling the measure in the scales is actually a teaching that is not only regulated in Islam. Even long before the advent of Islam, the demand to be fair in giving measurements and weights had become a living norm in society. However, it is not a guarantee to ensure a fair attitude in fulfilling the measurements and the scales are immediately applied in the trading activity by the traders. Furthermore, Islam conveys messages on the importance of fulfilling the measurements in the scales through the Koran which are contained in surah al-Isra ': 35, Hud: 84 and Surat al-'Araf: 34 with various approaches, namely in the form of story editorial, then the orders and prohibitions come to reveal the domino effect that is born as a result of fraudulent actions in measuring and weighing. The method used in this discussion is first to describe the meaning of the language contained in the verse, then to explain the interpretation of the verse from the various opinions of the commentators and finally to provide conclusions from the various views of the commentators. Keywords: Business Ethics, Tafsir al-Qur'an, Fulfilling the Measures.